ANALISIS MANAJEMEN TI MENGGUNAKAN METODE GOAL QUESTION METRIC - Vito Triantori (LPPM Nusa Mandiri, 2017)
The more computer education in schools needed to make-not only in terms of education but reliable computer support is needed. In order to maximize the computer to the precision and accuracy of the data is as well very important. Similarly, the Institute of Computer Education PesonaEdu learning school that has many partners and grow more led to the Division of Information and Technology PesonaEdu iLearning continue to develop techniques to improve the quality management system so as to the future can be the data to support decision-making at the management Appropriate levels and handling. In this case, study to discuss the management related to the management of computers is in school partner PesonaEdu iLearning. By using the IT Infrastructure Library (ITIL) as a basis for improving the quality management system. The methodology covers Among other things produced comparative analysis before and after implementation of improvement, based on the method Goal Question Metric.